2022
DOI: 10.3389/fimmu.2022.997589
|View full text |Cite
|
Sign up to set email alerts
|

Cytopenia after chimeric antigen receptor T cell immunotherapy in relapsed or refractory lymphoma

Abstract: BackgroundPatients with relapsed or refractory (R/R) lymphomas have benefited from chimeric antigen receptor (CAR)-T-cell therapy. However, this treatment is linked to a high frequency of adverse events (AEs), such as cytokine release syndrome (CRS), immune effector cell-associated neurotoxicity syndrome (ICANS), and hematologic toxicity. There has been increasing interest in hematological toxicity in recent years, as it can result in additional complications, such as infection or hemorrhage, which remain intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…CD8+ T‐cells and CD56+ natural killer (NK) cells fully recovered in all patients by 1 year, while reconstitution of CD4+ T cells was delayed, with normalization in only 67% of patients at 1 year. Similarly, in 39 CAR‐T recipients with R/R, the absolute counts of CD4+, CD8+, and CD16/56+ lymphocytes decreased significantly after lymphodepleting chemotherapy: while CD8+ and CD16/CD56+ cell counts rapidly recovered in all patients at a median time of 21 days, 7–10,12–15,17,21,22,24–64,66–92 a slower recovery was observed for CD4+, which recovered within 60 days in only 5 (23.81%) of patients 71 …”
Section: Immune Reconstitutionmentioning
confidence: 90%
See 2 more Smart Citations
“…CD8+ T‐cells and CD56+ natural killer (NK) cells fully recovered in all patients by 1 year, while reconstitution of CD4+ T cells was delayed, with normalization in only 67% of patients at 1 year. Similarly, in 39 CAR‐T recipients with R/R, the absolute counts of CD4+, CD8+, and CD16/56+ lymphocytes decreased significantly after lymphodepleting chemotherapy: while CD8+ and CD16/CD56+ cell counts rapidly recovered in all patients at a median time of 21 days, 7–10,12–15,17,21,22,24–64,66–92 a slower recovery was observed for CD4+, which recovered within 60 days in only 5 (23.81%) of patients 71 …”
Section: Immune Reconstitutionmentioning
confidence: 90%
“…In a recent retrospective study of 133 patients, lomustine/etoposide/cytarabinebased lymphodepletion, and prior HSCT were independently associated with early thrombocytopenia, but not with late hematologic toxicity. 15 Prior bone marrow infiltration and the number of prior lines of chemotherapy and/or radiotherapy may also contribute to bone marrow dysfunction and lead to persistent cytopenias after CAR-T therapy. 8,10,12,15,25…”
Section: Factors Related To Patients Previous Treatments and Hematopo...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the role of lymphodepleting therapy needs to be further studied in this context [110]. Reasonable application of corticosteroids and toci for CRS is also important, as persistent CRS appears to be a common risk factor for severe early cytopenia [111].…”
Section: Prevention and Managementmentioning
confidence: 99%
“…In addition, J. Zhou et al. ( 37 ) retrospectively analyzed 133 patients with R/R lymphoma who received CAR-T cells therapy. Studies have found that severe neutropenia, anemia, and thrombocytopenia frequently occur after CAR-T cells infusion.…”
Section: Clinical Presentation Of Saes Associated With Car-t Cells Th...mentioning
confidence: 99%